Differences in infection control and diagnostic measures for multidrug-resistant organisms in the tristate area of France, Germany and Switzerland in 2019: survey results from the RH(E)IN-CARE network - Tschudin Sutter, Sarah; Lavigne, Thierry; Grundmann, Hajo; Rauch, Julia; Eichel, Vanessa; Deboscker, Stéphanie; Jaulhac, Benoit; Mutters, Nico T. (Swiss medical weekly, 2021)
Multidrug-resistant organisms are a public health threat. Single-centre interventions, however, are likely to fail in the long term, as patients are commonly transferred between institutions given the economic integration across borders. A transnational approach targeting larger regions is needed to plan overarching sets of interventions.